2001
DOI: 10.1007/s00037-001-8192-0
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Positivstellensatz proofs for the knapsack

Abstract: A lower bound is established on degrees of Positivstellensatz calculus refutations (over a real field) introduced in (Grigoriev & Vorobjov 2001; Grigoriev 2001) for the knapsack problem. The bound depends on the values of coefficients of an instance of the knapsack problem: for certain values the lower bound is linear and for certain values the upper bound is constant, while in the polynomial calculus the degree is always linear (regardless of the values of coefficients) (Impagliazzo et al. 1999).This shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
124
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(124 citation statements)
references
References 15 publications
0
124
0
Order By: Relevance
“…By now, there's a large body of work that establishes lower bounds on SoS SDP for various average case problems. Beginning with the work of Grigoriev [Gri01a], a long line work have established tight lower bounds for random constraint satisfaction problems [Sch08,BCK15,KMOW17] and planted clique [MPW15, DM15, HKP15, RS15, SDP lower bounds for the planted clique problem were known for smaller degrees of sum-of-squares relaxations and for other SDP relaxations before; see the references therein for details.…”
Section: Related Workmentioning
confidence: 99%
“…By now, there's a large body of work that establishes lower bounds on SoS SDP for various average case problems. Beginning with the work of Grigoriev [Gri01a], a long line work have established tight lower bounds for random constraint satisfaction problems [Sch08,BCK15,KMOW17] and planted clique [MPW15, DM15, HKP15, RS15, SDP lower bounds for the planted clique problem were known for smaller degrees of sum-of-squares relaxations and for other SDP relaxations before; see the references therein for details.…”
Section: Related Workmentioning
confidence: 99%
“…This polynomial is nonnegative on all x ∈ {0, 1} n , and the induced matrix M g (x, y) = g(x ∧ y) is a submatrix of the slack matrix of the correlation polytope by Lemma 5. For odd n, Grigoriev [Gri01] shows that the sum-of-squares degree of g is n 2 (see also [Lau03]). Blekherman et al [BGP14] show that g even has high rational sum-of-squares degree: if the product pg has sos degree d, where p is an sos polynomials of degree r, then r + d ≥ 1 While we know that q is nonnegative on [n], we will not use this information.…”
Section: Quantum Query Complexity Lower Boundmentioning
confidence: 99%
“…Most of the known lower bounds for the hierarchy originated in the works of Grigoriev [17,18] (also independently rediscovered later by Schoenebeck [36]). In [18] it is shown that random 3XOR or 3SAT instances cannot be solved by even Ω(n) rounds of SoS hierarchy.…”
Section: Introductionmentioning
confidence: 99%
“…Grigoriev [17] showed that n/2 levels of Lasserre are needed to prove that the polytope {x ∈ [0, 1] n | n i=1 x i = n/2 + 1/2} contains no integer point. A simplified proof can be found in [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation